PELATIHAN PEMBUATAAN SABUN PADAT ALAMI UNTUK MENINGKATKAN KETERAMPILAN DAN KEMANDIRIAN EKONOMI DI KAF GEDEBAGE - Cengristitama Cengristitama; Yusi Prasetyaningsih; Irma Nuril Maryam; Ratna Rizky Wulandari (ASOSIASI IDEBAHASA KEPRI, 2026)
Community empowerment is a crucial strategy for increasing self-reliance in facing current social and economic challenges. One crucial aspect of this empowerment is the development of skills and expertise that can directly benefit the community. Soap, a daily necessity, is generally produced through a chemical process. Soap consists of a mixture of several chemicals processed through a transesterification or saponification reaction. Currently, there are various types of soap available, and if the ingredients are not used appropriately, they can cause side effects, such as dry skin or irritation. The purpose of this outreach program is to provide training in making solid soap within the Kuttab Al Fatih (KAF) Gedebage Islamic boarding school environment, to achieve economic independence, and to educate students about selecting the right, safe composition using natural ingredients. The results showed that the training participants were able to understand the soap-making process, select the appropriate and safe ingredient composition, and produce soap independently. Furthermore, a soap community was formed that receives regular mentoring, thereby reducing dependence on commercial products.